2024
DOI: 10.1101/2024.02.23.581770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial origins of the pressure to sleep

Raffaele Sarnataro,
Cecilia D. Velasco,
Nicholas Monaco
et al.

Abstract: SummaryThe neural control of sleep requires that sleep need is sensed during waking and discharged during sleep. To obtain a comprehensive, unbiased view of molecular changes in the brain that may underpin these processes, we have characterized the transcriptomes of single cells isolated from rested and sleep-deprived flies. Transcripts upregulated after sleep deprivation, in sleep-control neurons projecting to the dorsal fan-shaped body (dFBNs) but not ubiquitously in the brain, encode almost exclusively prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 104 publications
1
0
0
Order By: Relevance
“…For instance, we found that mitochondrial and OXPHOS genes are downregulated by clock disruption and reinstated by co-inhibition of DREAM also in human cells (Figure 6E and 6F; Table S22), revealing mitochondria and OXPHOS as the most consistently clock-regulated entities across species and cell types. Interestingly, this observation is consistent with the recently discovered key involvement of mitochondria and OXPHOS in the induction of sleep and damage clearance during sleep 62,63 . Moreover, ribosome and ribosome biogenesis genes, and genes encoding the components of the transcriptional machinery showed opposite expression dynamics between clock-disrupted and DREAM co-inhibited cells (Figure S12D-F; Table S23).…”
Section: Mainsupporting
confidence: 91%
“…For instance, we found that mitochondrial and OXPHOS genes are downregulated by clock disruption and reinstated by co-inhibition of DREAM also in human cells (Figure 6E and 6F; Table S22), revealing mitochondria and OXPHOS as the most consistently clock-regulated entities across species and cell types. Interestingly, this observation is consistent with the recently discovered key involvement of mitochondria and OXPHOS in the induction of sleep and damage clearance during sleep 62,63 . Moreover, ribosome and ribosome biogenesis genes, and genes encoding the components of the transcriptional machinery showed opposite expression dynamics between clock-disrupted and DREAM co-inhibited cells (Figure S12D-F; Table S23).…”
Section: Mainsupporting
confidence: 91%

A half-centre oscillator encodes sleep pressure

Hasenhuetl,
Sarnataro,
Vrontou
et al. 2024
Preprint
Self Cite